TRLS-05. EARLY RESULTS FROM A PROSPECTIVE PHASE I/II DOSE ESCALATION STUDY OF NEOADJUVANT RADIOSURGERY FOR BRAIN METASTASES. (12th August 2019) - Murphy, Erin; Yang, Kailin; Suh, John; Yu, Jennifer; Schilero, Cathy; Mohammadi, Alireza; Stevens, Glen; Angelov, Lilyana; Vogelbaum, Michael; Barnett, Gene; Ahluwalia, Manmeet; Neyman, Gennady; et al.
Abstract: OBJECTIVES: Single-session stereotacic radiosurgery (SRS) alone for brain metastases larger than 2cm in maximal dimension results in local control of only 50%. Surgical resection followed by SRS to the resection cavity can result in leptomeningeal failure (LMD). This Phase I/II study aims to determine the safety and local control of neoadjuvant SRS at escalating doses followed by surgical resection of brain metastases greater than 2 cm. METHODS: Radiosurgery dose was escalated at 3 Gy increments from currently accepted RTOG standard. If no dose-limiting toxicities (DLT) were observed, the dose was escalated. Patients underwent surgical resection of brain metastases within 2 weeks and were followed with brain MRIs and neurologic evaluations every 3 months. RESULTS: 27 patients were enrolled. For tumor size >2.0–3.0 cm, 2 patients completed treatment at 18 Gy and 3 patients at 21Gy. For tumor size >3.0–4.0 cm, 4 patients were treated at 15 Gy and 9 patients were treated at 18 Gy and 1 patient at 21 Gy. For tumor size >4.0–5.0 cm, 1 patient was treated at 12 Gy and 7 patients at 15 Gy. No DLT have occurred. With a mean follow-up of 13.1 months, the 6 and 12 month local control was 93.8% and 72.3%, respectively. Six and 12 month distant brain control was 38.6% and 25.8%. Overall survival at 12 months was 53.5%. One patient developed LMD 5 months following SRS. 4 patients (15%) had acute grade 1/2 toxicity, and no grade 3/4 toxicity was observed. CONCLUSIONS: Neoadjuvant SRS with dose escalation followed by surgical resection for brain metastases greater than 2 cm results in local control comparable to postoperative SRS or WBRT, and demonstrates acceptable acute toxicity. A low rate of LMD failure was found. The Phase II portion of the trial will be conducted at the maximum tolerated SRS doses.